Koncepcja rodziny w przestrzeni litewskiej polityki rodzinnej - Targamadzé, Vilija (Oficyna Wydawnicza ATUT - Wrocławskie Wydawnictwo Oświatowe, 2012)
The family, its conceptualization and functioning, as well as family policy are discussed at the personal, community and state level. This makes sense because different cultural, historical, ethical, social and other alternations affect the assessment and evaluation of these three significant components. Besides family policy is a very important part of public policy in a state, what makes obvious impact on every human life (even those who are living not in a family). The aim of this article is to shed light on the concept of family, family functioning and family policy as three mutually interacting components in a unified narrative.
Keywords: family; conception of the family; Lithuanian family policy